An Examination of Jumia as a Business Entity Under Islamic Business Ethics - Saheed Badmus Suraju; Rukayah Yetunde Ayilara (Universitas Muhammadiyah Yogyakarta, 2022)
In the 21st century, online access has become widespread and inclusive to the point of making business easy for most people to survive in contemporary society. Series of online trading are available to raise money for people, including Muslims, without considering the business Ethics from Islamic Perspective while patronizing online trading. On this note, this paper examines the business operation of an online business entity from the point of view of Islamic business ethics with a view to using Jumia as a case study. The research findings show that there are non-SharÄ«a compliance operations in the online transaction of Jumia. It is also revealed that the Muslims patronizing Jumia business is not concerned about Islamic business ethics in their transaction. The paper concludes by advocating the application of Islamic business ethics in all transactions in which the Muslims will be involved in general and particularly in Jumia online services to give room for more Muslims to patronize the platform.